Case of Hemorrhagic Vasculitis with Difficult Stream of 9 Years Old Boy - A. A. Lebedenko; A. M. Saryuchev; E. V. Nosova (Медицинский вестник Юга России, 2012)
We are presenting a case of hemorrhagic vasculitis with difficult stream of 9 years old boy. Feature of this case is manifestation of the disease after quinsy with pronounced lymphoproliferative syndrome (enlargement of anterior and posterior cervical and submandibular lymph nodes up to 12-15 mm in diameter), which made it necessary to conduct a differential diagnosis with lymphoproliferative disorders. Thereby the biopsy of lymph node was made. Another feature was that with hemorrhagic rash on lower extremities extensive necrosis were developed, accompanied by severe pain and no analgesic effect. Later joined abdominal and renal syndromes, with development of cruel nephritis. The therapy allowed to achieve clinical remission, however the urinary syndrome retained for long. After correction of the therapy (sandimmun) there were marked rapid positive changes.